2002
DOI: 10.1002/ca.1101
|View full text |Cite
|
Sign up to set email alerts
|

Measuring movement at the low back

Abstract: The clinical importance of movements of the human spine is increasingly being realized but their measurement is difficult to carry out. Traditionally, measurement of spinal motion focuses on the lumbar spine as the mobile region and movement at the lower thoracic spine is largely ignored. The aim of this study was to test the hypothesis that sagittal movement at the low back is not confined to the lumbar spine. The range of sagittal movement and the amount of skin distraction during trunk flexion was studied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…3D marker clusters adapted and based upon the design of previous investigations 5,23,24 were placed over the spinous processes of T3, T8 and L3 and were used to track movement in the upper thoracic (UT), lower thoracic (LT) and lumbar (L) region of the spine, respectively (Figure 1(a)). Each 3D cluster consisted of a silicone base plate and three non-collinear reflective markers attached to plastic tubing, fixed to the skin using double sided adhesive tape ( Figure 1(b)).…”
Section: Methodsmentioning
confidence: 99%
“…3D marker clusters adapted and based upon the design of previous investigations 5,23,24 were placed over the spinous processes of T3, T8 and L3 and were used to track movement in the upper thoracic (UT), lower thoracic (LT) and lumbar (L) region of the spine, respectively (Figure 1(a)). Each 3D cluster consisted of a silicone base plate and three non-collinear reflective markers attached to plastic tubing, fixed to the skin using double sided adhesive tape ( Figure 1(b)).…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] Following this research direction, the next target is to develop a normative database of lumbar spinal motion. This is because pathologic spinal motion can be identified only if "normal" spinal motion is defined.…”
mentioning
confidence: 99%
“…The upper thoracic mount was stuck to the skin 5-10 cm inferior to the vertebra prominens at the base of the neck. We have previously demonstrated that the skin at this site maintains a constant relationship with the underlying skeleton (Rice et al, 2002). The pelvic construct was attached to the pelvis as described above and a mount of three LED markers attached to it.…”
Section: D Motion Analysis Systemmentioning
confidence: 99%
“…We have demonstrated previously that sagittal movement of the lower spine involves not only movement of the lumbar region but also movement of the lower part of the thoracic spine (Rice et al, 2002). In that study, we proposed that the "functional low back" extends from the sacrum to the mid-thoracic spine and that movement of this region can be regarded as the movement between the immobile section of the thoracic spine and the pelvis.…”
Section: Introductionmentioning
confidence: 96%